2019
DOI: 10.1039/c8cc08940j
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule reaction networks that model the ROS dynamics of the rhizosphere

Abstract: Molecules released by plants and bacteria form complex abiotic reaction diffusion networks that might regulate the ROS dynamics along the roots of the plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…It has been observed that rhizosphere bacteria are exposed to high levels of reactive oxygen species (ROS) that are formed along the plant root surface during the reaction of redox-active plant secondary metabolites, such as phenols, quinones, flavins, and phenazines, with molecular oxygen [ 90 ]. Additionally, upon contact with bacteria, one of the plant defense reactions is the production of ROS, nitric oxide and phytoalexins; thus, rhizosphere bacteria must survive in a highly oxidative environment during the colonization of plant tissues.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that rhizosphere bacteria are exposed to high levels of reactive oxygen species (ROS) that are formed along the plant root surface during the reaction of redox-active plant secondary metabolites, such as phenols, quinones, flavins, and phenazines, with molecular oxygen [ 90 ]. Additionally, upon contact with bacteria, one of the plant defense reactions is the production of ROS, nitric oxide and phytoalexins; thus, rhizosphere bacteria must survive in a highly oxidative environment during the colonization of plant tissues.…”
Section: Resultsmentioning
confidence: 99%
“…[4] Initially, ROS were recognized as integral to adversarial immune interactions: host cells generate ROS to defend against pathogen threats while microbes respond to ROS by upregulating antioxidant defense mechanisms. More recently, the biological role of ROS has been expanded beyond adversarial hostpathogen interactions and now ROS are believed to be broadly important in the communication between a host and its microbiome (e.g., between the gut epithelium and its microbiome, [5][6][7] or between the root and its rhizosphere community [8][9][10] ). Interestingly, phenolics are often believed to play an important but incompletely understood, role in redox-based interactions.…”
Section: Doi: 101002/adma202007758mentioning
confidence: 99%
“…Redox cycling between quinones and hydroquinones occurs in the rhizosphere with a great impact on plant-microbe interactions (Taran et al, 2019). Such redox cycling is known to be used as a lignocellulolytic agent by wood-decaying brown rot fungi.…”
Section: Roles Of Hifs In Host-parasitic Plant Interactions After Prementioning
confidence: 99%